(untitled) (Marketing Jurnali, 2025)
This study examines how social media influencers affect consumer buying behavior in the electronics market. It focuses on three main influencer attributes — credibility, attractiveness, and expertise — that shape trust and purchase intention. The findings highlight that social media acts as a key driver of decision-making in the digital economy.